2016
DOI: 10.4236/ce.2016.77100
|View full text |Cite
|
Sign up to set email alerts
|

ICTs in the Classroom, Multiliteracy and Special Education: A Required Interface

Abstract: Many children have special difficulties to interact with their counterparts, but use tablets and smartphones with resourcefulness. Cards with graphic symbols are very useful to assist communication. However, the teacher who works in a classroom with forty students in Brazil does not have time to train the special student to properly use this alternative means of communication. Therefore, this research developed and tested an application installed on a smartphone, which identified the communication card and ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Research shows that teachers who receive SEN students in their classrooms argue, with some justification, that these students cannot follow regular school lessons due to the lack of appropriate material and assistive technology (Correia, 2008a; Moreira and Manrique, 2014a; Young and Curcic, 2013; Carneiro et al ., 2015; Manrique et al ., 2016). Others relate the lack of initial and further training to equip teachers with the skills to deal with such situations (Correia, 2008b; Mantoan, 2008; Moreira, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that teachers who receive SEN students in their classrooms argue, with some justification, that these students cannot follow regular school lessons due to the lack of appropriate material and assistive technology (Correia, 2008a; Moreira and Manrique, 2014a; Young and Curcic, 2013; Carneiro et al ., 2015; Manrique et al ., 2016). Others relate the lack of initial and further training to equip teachers with the skills to deal with such situations (Correia, 2008b; Mantoan, 2008; Moreira, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned, educational agents’ attitudes are one of the great challenges in the achievement of inclusive education, since they can constitute either a facilitator or a barrier [ 60 , 61 , 62 , 63 , 64 ]. Thus, teachers’ attitudes, composed of three dimensions—cognitive (beliefs), affective (feelings) and behavioral (actions) [ 60 ]—are essential to achieve educational quality [ 2 ], although it should be noted that sometimes teachers are not sufficiently aware of the diversity of the needs of their students with disabilities [ 24 ]. Concerning self-efficacy, it has been reported that teachers with higher levels show greater job satisfaction, while those with lower levels of confidence in their abilities are associated with increased work-related stress and difficulties in coping with their tasks, including dealing with disruptive behaviors [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is a need to rebuild schools and promote inclusion through consensual decisions and critical reflection [ 23 ]. Among the barriers expressed by teachers, one can note their belief that these students are unable to follow normal school classes due to a lack of appropriate materials and assistive technology [ 24 , 25 ] or the lack of initial and ongoing preparation to face the diversity of challenges with these students [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of making optimal use of AAC devices, while producing a more affordable tool, AAC applications (app) were created. (Manrique et al, 2016). This is a significant milestone for AAC app growth, that also extended to the academic and scientific communities (Light and McNaughton, 2012).…”
Section: Aacvox: Mobile Application For Augmentative Alternative Commmentioning
confidence: 95%